Pengembangan Rancangan Pembelajaran Profesi Keguruan dengan Kulsponsi di Perguruan Tinggi - A.Supriyanto dkk A.Supriyanto dkk (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Developing Profesi Keguruan Learning Design with Kulsponsi in Higher Education. The study was intended to develop a learning design in Profesi Keguruan with kulsponsi in highereducation, especially to improve attention, activity, and comprehension of students in learning. An action research approach was used in this study. The subjects were students following Profesi Keguruan course offering. The results showed that kulsponsi design can improve the attention, activity, and comprehension of the students.